MEDICINAL PLANTS AND PHYTOCHEMICALS IN PREVENTION AND MANAGEMENT OF LIFE STYLE DISORDERS: PHARMACOLOGICAL STUDIES AND CHALLENGES - SINGH, SHALU; JAIN, VINEET; JAIN, SWATANTRA KUMAR; CHANDRA, KAILASH (Asian Journal of Pharmaceutical and Clinical Research, 2021)
The prevalence of lifestyle disorders such as hypertension, diabetes mellitus (DM), dyslipidemia, and overweight/obesity is rising rapidly. Recently the popularity of herbal supplements among patients with lifestyle disorders has been increasing. Consumption of a plant-based diet consisted of appropriate phytochemicals has been accepted as a reliable means for the prevention and management of several disorders. Phytochemicals play a crucial role in disease prevention, especially when lifestyle changes alone are not found effective. Various human and animal trials have established the pharmacological action of phytonutrients present in herbal plants. Several bioactive compounds such as polyphenols, flavonoids, alkaloids, and stilbenes. are present in plants such as garlic, Aloe vera, turmeric, tulsi, and drumstick. that have shown a significant beneficial effect on DM, metabolic syndrome, lipid disorders, etc. This review focuses on the therapeutic effect of some of the high potential herbal plants and their phytochemicals in the management of lifestyle disorders and the challenges with the use of herbal medicines.